Piezoelectric Nylon‐11 Nanowire Arrays Grown by Template Wetting for Vibrational Energy Harvesting Applications. (11th November 2016) - Datta, Anuja; Choi, Yeon Sik; Chalmers, Evie; Ou, Canlin; Kar‐Narayan, Sohini
Abstract : Piezoelectric polymers, capable of converting mechanical vibrations into electrical energy, are attractive for use in vibrational energy harvesting due to their flexibility, robustness, ease, and low cost of fabrication. In particular, piezoelectric polymers nanostructures have been found to exhibit higher crystallinity, higher piezoelectric coefficients, and "self‐poling, " as compared to films or bulk. The research in this area has been mainly dominated by polyvinylidene fluoride and its copolymers, which while promising have a limited temperature range of operation due to their low Curie and/or melting temperatures. Here, the authors report the fabrication and properties of vertically aligned and "self‐poled" piezoelectric Nylon‐11 nanowires with a melting temperature of ≈200 °C, grown by a facile and scalable capillary wetting technique. It is shown that a simple nanogenerator comprising as‐grown Nylon‐11 nanowires, embedded in an anodized aluminium oxide (AAO) template, can produce an open‐circuit voltage of 1 V and short‐circuit current of 100 nA, when subjected to small‐amplitude, low‐frequency vibrations. Importantly, the resulting nanogenerator is shown to exhibit excellent fatigue performance and high temperature stability. The work thus offers the possibility of exploiting a previously unexplored low‐cost piezoelectric polymer for nanowire‐based energy harvesting, particularly at temperatures well above room temperature. Abstract : Vertically aligned arrays of piezoelectric Nylon‐11 nanowires with high aspect ratio are prepared using a capillary template wetting method within nanoporous anodized alumina templates. The template‐grown nanowires are "self‐poled" and thus can be directly incorporated into nanogenerators with excellent fatigue performance. The relatively high melting temperature (≈200 °C) of these nanowires makes them suitable for energy harvesting applications at elevated temperatures.